IMPLEMENTASI METODE SMART (SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE) UNTUK PENILAIAN KINERJA GURU BERBASIS WEB - Hadi Prayitno, Muhammad; sucipto, hadi (Inovate, 2025)
Abstract Objective and transparent teacher performance appraisal is very important to improve the quality of education. This research aims to develop a web-based teacher performance appraisal system using the SMART (Simple Multi-Attribute Rating Technique) method at SMK 10 November Jombang. The system allows assessment based on four main criteria: Pedagogic (40%), Personality (20%), Social (20%), and Professional (20%), with 14 indicators to assess teacher performance. The results show that the application of the SMART method in a web-based system can improve the objectivity and transparency of the assessment. Teachers with the highest utility scores such as Eti Pertiwisasi, S.Pd, Desy H Arini, S.Kom, Deny Saputro, S.Kom, and Angga Setiya Budi, S.Kom scored 1.00, while Anggit Kinanti, S.Pd scored 0.93. The system also supports more objective decision-making and provides constructive feedback for teachers' professional development. The results of this system compared to manual calculations show high consistency. This research is expected to contribute to improving the quality of teacher performance appraisal and the quality of education at SMK 10 November Jombang. Keywords: Teacher performance appraisal, SMART, web-based system, objectivity, transparency. DAFTAR PUSTAKA Akram, M., Munir, F., & Ahmad, B. (2021). Effect of Teacher Performance Evaluation on School Effectiveness. Sir Syed Journal of Education & Social Research (Sjesr), 4(1), 431–439. https://doi.org/10.36902/sjesr-vol4-iss1-2021(431-439) Alfi Azqia Uzzulfa Haq, Tanhella Zein Vitadiar, I Kadek Dwi Nuryana, & Muhammad Fatkhur Rizal. (2024). SISTEM PENDUKUNG KEPUTUSAN PERKEMBANGAN BELAJAR ANAK TK EL-YAMIEN 1 TUBAN MENGGUNAKAN METODE SMART BERBASIS WEB. Inovate : Jurnal Ilmiah Inovasi Teknologi Informasi, 9(1), 173–181. https://doi.org/10.33752/inovate.v9i1.7270 Astriani, M., Indah, F. S., & Seri, H. (2023). Pengukuran Kinerja Guru Di SMP Nurul Qomar Palembang Di Era Kurikulum 2013 Dan Selama Pandemi Covid-19. Jurnal Sains Dan Edukasi Sains. https://doi.org/10.24246/juses.v5i2p81-86 Borja, P. J. E. (2024). The Evaluation of Teacher Professional Performance, Engine of Performance. International Journal of Human Sciences Research, 4(18), 2–6. https://doi.org/10.22533/at.ed.5584182431055 Coffin, T. B., Bowen, D. J., Swisher, E. M., Lu, K. H., Rayes, N., Norquist, B. M., Blank, S. V., Levine, D. A., Bakkum‐Gamez, J. N., Fleming, G. F., Olopade, O. I., D’Andrea, A. D., Nebgen, D., Peterson, C. B., Munsell, M. F., Gavin, K., Lechner, R., Crase, J., Polinsky, D., & Romero, I. L. (2022). An Accessible Communication System for Population-Based Genetic Testing: Development and Usability Study. Jmir Formative Research, 6(10), e34055. https://doi.org/10.2196/34055 Darmawan, R., Andriani, A., Fatkhur Rizal, M., & Widoyoningrum, S. (2024). SISTEM PENDUKUNG KEPUTUSAN PELANGGARAN TATA TERTIB SANTRI MENGGUNAKAN METODE SMART. Inovate : Jurnal Ilmiah Inovasi Teknologi Informasi, 9(1), 10–17. https://doi.org/10.33752/inovate.v9i1.7230 Demir, K. A. (2021). Smart Education Framework. Smart Learning Environments, 8(1). https://doi.org/10.1186/s40561-021-00170-x Dharmawan, D. (2024). Application of TOPSIS Method to Design a Decision Support System in Assessing Teachers Performance. Jurnal Informasi dan Teknologi, 64–69. https://doi.org/10.60083/jidt.v6i1.474 Ford, T. G., & Hewitt, K. K. (2020). Better Integrating Summative and Formative Goals in the Design of Next Generation Teacher Evaluation Systems. Education Policy Analysis Archives, 28, 63. https://doi.org/10.14507/epaa.28.5024 Jiang, J., & Wang, H. (2023). Design of Evaluation Index System for Smart Classroom Learning Activities Based on Multimodal Data. 345–356. https://doi.org/10.2991/978-94-6463-242-2_43 Karyaningsih, D. (2023). Decision Support System for Teacher Performance Assessment Using the Weighted Product Method. International Journal of Information Technology and Computer Science Applications, 1(2). https://doi.org/10.58776/ijitcsa.v1i2.21 Kundra, S., Jha, N., & Dhiman, S. (2024). Association of Ergonomics and Musculoskeletal Disorders Among School Teachers. International Journal of Science and Research Archive, 11(1), 1598–1604. https://doi.org/10.30574/ijsra.2024.11.1.0205 Li, W., & Fan, X. (2021). Construction of Network Multimedia Teaching Platform System of College Sports. Mathematical Problems in Engineering, 2021, 1–11. https://doi.org/10.1155/2021/6304703 Liu, M., Zhou, R., Dai, J., & Feng, X. (2022). Analysis and Practice of Using Modern Information Technology for Classroom Teaching Mode Reform. Mobile Information Systems, 2022, 1–8. https://doi.org/10.1155/2022/2565735 Lumbangaol, S. K., Nababan, E. B., & Lydia, M. S. (2022). Sistem Pendukung Keputusan Penilaian Kinerja Guru Selama Pembelajaran Daring menggunakan Metode Vikor. JURNAL MEDIA INFORMATIKA BUDIDARMA, 6(2), 1153. https://doi.org/10.30865/mib.v6i2.3798 Lungu, S., & Daka, H. (2022). Internal Monitoring and Evaluation of Teaching in Secondary Schools of Kabwe District in Central Province, Zambia. Challenges and Possible Solutions. International Journal of Research and Innovation in Social Science, 06(01), 180–186. https://doi.org/10.47772/ijriss.2022.6114 Radnaa, N., Davaa, A., Dashzeveg, T., & Purevsuren, T. (2021). Development of Concept Model for Evaluation, Enhancement and Promotion of University Teachers. https://doi.org/10.15405/epsbs.2021.07.02.6 Setiawan, W., Nurwahid Pranoto, & Khoirul Huda. (2020). Employee Performance Evaluation Decision Support System with the SMART (Simple Multi-Attribute Rating Technique) Method. Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 4(1), 50–55. https://doi.org/10.29207/resti.v4i1.1384 Sumer, S., & Abou, S. (2020). The Uses of Smart Devices in Teaching English for Palestine. International Journal on Studies in English Language and Literature, 8(2). https://doi.org/10.20431/2347-3134.0802002 Tridora, V. A., Badaruddin, K., & Amilda, A. (2021). The Strategi Kepala SD-LB dalam Meningkatkan Kinerja Guru. Studia Manageria, 3(1), 53–68. https://doi.org/10.19109/studiamanageria.v3i1.7337 Wibowo, F. (2023). Adopsi Teknologi SMART (Simple Multi-Attribute Rating Technique) Dalam Penilaian Kinerja Karyawan. Entrepreneurship Bisnis Manajemen Akuntansi (E-Bisma), 340–349. https://doi.org/10.37631/ebisma.v4i2.1184 Yan, L., & Guo, Y. (2021). Research on the Strategy of Smart Classroom Construction Based on Teachers’ Data Literacy. SHS Web of Conferences, 123, 01017. https://doi.org/10.1051/shsconf/202112301017 Zhang, M., & LI, W.-P. (2021). An Automatic Classification Method of Sports Teaching Video Using Support Vector Machine. Scientific Programming, 2021, 1–8. https://doi.org/10.1155/2021/4728584 Zhang, S., & Zhou, A. (2023). The Construction and Practice of a TPACK Development Training Model for Novice University Teachers. Sustainability, 15(15), 11816. https://doi.org/10.3390/su151511816